A case of miliary tuberculosis following transurethral surgery and prostate biopsy after intravesical Bacillus Calmette–Guerin immunotherapy. Issue 1 (3rd October 2021) - Kurokawa, Yoshiaki; Kawai, Taketo; Miyakawa, Jimpei; Makise, Naohiro; Akiyama, Yoshiyuki; Yamada, Yuta; Sato, Yusuke; Yamada, Daisuke; Ushiku, Tetsuo; Kume, Haruki
Abstract : Introduction: Intravesical Bacillus Calmette–Guerin immunotherapy is known to prevent recurrence of bladder cancer, but it can cause tuberculosis infections as an adverse event. Case presentation: A 75‐year‐old man visited our hospital due to hematuria. The patient was diagnosed with bladder cancer and underwent transurethral resection of the bladder tumor. Postoperatively, the patient received Bacillus Calmette–Guerin immunotherapy. One year later, we performed transurethral surgery and prostate biopsy because of cystoscopic findings showing nodulous lesions in the bladder and an elevated serum prostate‐specific antigen level. The patient presented with high fever and malaise since the surgery. After careful examination, the patient was diagnosed with miliary tuberculosis caused by Mycobacterium bovis . The pathology of the bladder and prostate revealed acid‐fast bacilli collection by Ziehl–Neelsen staining. Conclusion: The surgery exacerbated the local infection into a systemic infection. The risk of developing miliary tuberculosis should be considered at transurethral surgery or prostate biopsy in patients after intravesical Bacillus Calmette–Guerin immunotherapy.